Nanocomposites: Glassomer—Processing Fused Silica Glass Like a Polymer (Adv. Mater. 22/2018). Issue 22 (May 2018) - Kotz, Frederik; Schneider, Norbert; Striegel, Andreas; Wolfschläger, Andre; Keller, Nico; Worgull, Matthias; Bauer, Werner; Schild, Dieter; Milich, Marcel; Greiner, Christian; Helmer, Dorothea; Rapp, Bastian E.
Abstract : Glass is among the most important materials but is notoriously difficult to process, which is why polymers are usually preferred. In article number1707100, Bastian E. Rapp and co‐workers introduce "Glassomer" a solid nanocomposite that can be structured using polymer molding and subtractive manufacturing techniques and then converted to glass via thermal treatment, thus combining the outstanding material properties of glass with the simplicity of polymer processing.